Characteristics of fine particulate matter and volatile organic compounds in subway station offices in China. (15th January 2021) - Ji, Wenjing; Liu, Zhenzhe; Liu, Chenghao; Wang, Chunwang; Li, Xiaofeng
Abstract: The air quality in subway station offices can greatly affect the health and comfort of metro staff. We characterized the air pollution in the offices of six subway stations by measuring the concentrations and composition of airborne fine particulate matter and volatile organic compounds in both summer and winter. We compared the findings by season, ventilation system type, platform screen door design, and station age. Concentrations of metals in airborne particulate matter were higher in metro station offices than in reference ambient air, with iron, manganese, and copper greatly exceeding their concentrations in ambient air. The concentrations of total volatile organic compounds exceeded national standard limits and ranged from 1027.63 to 1801.83 μg/m 3 . Operating the mechanical ventilation system in full fresh-air mode rather than primary air return mode reduced the concentrations of volatile organic compounds. These findings provide an assessment of pollutant characteristics in metro station offices and may be useful in formulating prevention and mitigation strategies for indoor air quality management. Graphical abstract: Image 1 Highlights: We characterized airborne particles and volatile compounds in subway station offices. Constituents of airborne particles varied between station offices and ambient air. Fe, Mn, and Cu in station offices were much more abundant than in ambient air. Concentrations of volatile organic compounds exceeded recommended limits. Pumping fresh (not recycled) air can reduce the levels of volatile organic compounds.